Advances in pavement design through full-scale accelerated pavement testing : proceedings of the 4th International Conference on Accelerated Pavement Testing, Davis, CA, USA, 19-21 September 2012 /: proceedings of the 4th International Conference on Accelerated Pavement Testing, Davis, CA, USA, 19-21 September 2012. (©2012) - Unknown
No abstract available